Project-Based Learning for Fostering Students' Ecological Awareness: An Integration of Ecopedagogy and Islamic Ecotheology - Anggi Anggraini; Zuhri Zuhri; Sutiah Sutiah; Samsul Susilawati (Education and Sociedad Journal, 2025)
This study aims to analyze the effect of Project-Based Learning (PjBL), the ecopedagogical approach, and Islamic ecotheological values on students' ecological awareness, with PjBL products as a mediating variable in Fiqh learning at state Islamic high school. This study employed a quantitative explanatory approach using the SEM-PLS method. The sample consisted of 120 students selected through purposive sampling. Data were collected using questionnaires and project product assessment rubrics. The results show that PjBL (P-value < 0.001), the ecopedagogical approach (P-value = 0.004), and Islamic ecotheological values (P-value = 0.032) have a positive and significant effect on PjBL products. PjBL products also have a significant effect on ecological awareness (P-value = 0.001). However, PjBL (P-value = 0.089) and the ecopedagogical approach (P-value = 0.234) do not have a significant direct effect on ecological awareness, while Islamic ecotheological values remain significant (P-value = 0.032). Furthermore, PjBL products act as a full mediator in the relationship between PjBL and the ecopedagogical approach on ecological awareness but do not mediate the effect of Islamic ecotheological values. These findings indicate that ecological awareness is more effectively developed through learning experiences embodied in project products, while spiritual values have a direct influence on students' behaviour.